Internet addiction as a socio—psychological problem of society in the XXI century - M. А. Yuzhanin (Путеводитель предпринимателя, 2021)
The presented article analyzes the problems of the formation of Internet addiction in the modern information society. The author consistently examines the essence and characteristic signs (symptoms) of cyber addiction, socio–psychological prerequisites and factors of its actualization, the main forms of manifestation and social scale of distribution. Particular attention is paid to the issues of effective implementation of various types of prevention of pathological addiction to being in the worldwide network. As a result, it was concluded that it is necessary to systematically form (in the process of socialization of generations of the XXI century) a rationalized and balanced approach to the use of Internet resources and electronic digital devices that provide access to them. The ultimate goal of moving in this direction could be the development of a culture of healthy attitude and productive development of cyber technologies in the name of the liberation and progress of mankind, and not its enslavement and degradation.